Comprehension of Society and The Changes of Public Policies: Identifying Possible Triggers and Barriers - Robert STANESCU (Communications of International Proceedings, 2022)
Society itself it’s an ongoing developing and changing entity of which decision-making actors need to adopt uncommon, or unique, public policies in concordance with societies’ expectations in order to deliver adequate outcomes. In this regard, the scope of the article mainly does not focus on highlighting a peculiar public policy prognosis, but concentrates on promoting a different approach that clarifies current barriers and possible opportunities within society. Contemplated such as a guideline to discover peculiar barriers and triggers, the perspective also considers not to be an analysis of future public policies planification, but rather finding the path before the decision-making process, such as the conjunctures and not the outcomes. Moreover, discovering alternative paths and clues to comprehend, also will be beneficial to future research as well as for case studies within a given society, because withal society will develop at a swift phase.
Keywords: Society; decision-making actors; change and development; triggers and barriers